Experimental Analysis on Tensile Behavior of Engineered Cementitious Composite (ECC) using Polypropylene Fiber - Ali Raza Khoso; Muhammad Fahim; Shanker Lal Mehgwar; Muhammad Akram Akhund (Salehan Institute of Higher Education, 2018)
The high demand of tensile strength in concrete is always a critical issue for engineers, as 10% of the compressive strength is not sufficient to withstand higher loadings. Lesser ductility and strain capacity is another major issue of normal concrete. In the queue of modern researches, this paper is an attempt to study Engineered Cementitious Composite (ECC) from research of Professor Victor Li, the University of Michigan. ECC is an ultra-ductile cementitious composite which is highly crack resistant, with a high tensile strain capacity over that of normal concrete. The composite replaces coarse aggregates and fine aggregates by sand and fly ash respectively. ECC is made up of OPC, sand (passing from 250 µm and retained on 150µm), Fly Ash (Class F) with addition of Polypropylene fiber on different percentages i.e. 0%, 0.25%, 0.5%, 0.75%, 1.0% were studied. Tensile Strength of ECC was measured by casting & testing cylinders of 4”x 8” in Universal Testing Machine (UTM). The experimental results revealed that 111.40% increment in tensile strength was found at 0.5% PP fiber at ECC 1:1:1 and an increment of 74.74% was observed at ECC 1:0.8:1.2 at 1% PP fiber. The study concludes that this composite could substitute the normal concrete where high tension is the ultimate requirement with higher strain capacity.